2020
DOI: 10.21829/azm.2020.3612235
|View full text |Cite
|
Sign up to set email alerts
|

Estimación de cambios temporales de la condición corporal del borrego cimarrón (Ovis canadensis weemsi) a partir de fotointerpretación

Abstract: A partir de una escala de cinco puntos como método no invasivo, se analizaron imágenes obtenidas por foto trampeo, para visualizar partes corporales (espina dorsal, costillas y cadera) de los borregos, y detectar cambios estacionales de la condición corporal de machos y hembras evaluando el consumo de proteína obtenida a partir de su contenido en los forrajes. Se emplearon 20 cámaras trampa, ubicadas particularmente en cuerpos de agua superficiales. Se identificaron 199 animales en los dos años de muestreo; 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…This decision was made based on the results of the same study by Perry et al [43], who found that water catchments were the main congregation sites for bighorn sheep and therefore where the greatest number of records of the species could be obtained. In addition, the use of trail cameras, especially in water catchments, to monitor bighorn sheep populations has been used by other authors with good results [42]. It should be noted, however, that since the trail cameras were not distributed throughout the habitat available to the species in the study areas, the population size estimate obtained will only correspond to the region where the camera traps were placed, i.e., in the ejido Cordillera Molina, only the population in the central part of the Sierra Juárez will be estimated, while in the ejido Matomí, the estimate will be for the population inhabiting the coastal region of the Sierra Santa Isabel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This decision was made based on the results of the same study by Perry et al [43], who found that water catchments were the main congregation sites for bighorn sheep and therefore where the greatest number of records of the species could be obtained. In addition, the use of trail cameras, especially in water catchments, to monitor bighorn sheep populations has been used by other authors with good results [42]. It should be noted, however, that since the trail cameras were not distributed throughout the habitat available to the species in the study areas, the population size estimate obtained will only correspond to the region where the camera traps were placed, i.e., in the ejido Cordillera Molina, only the population in the central part of the Sierra Juárez will be estimated, while in the ejido Matomí, the estimate will be for the population inhabiting the coastal region of the Sierra Santa Isabel.…”
Section: Discussionmentioning
confidence: 99%
“…The last module includes ask to participants concerning about their participation in bighorn sheep monitoring, the purpose of the monitoring, the method used, the materials used, and the results obtained. After, a slide presentation was made to clarify the concept of wildlife monitoring, and to lay out and explain the correct implementation of the methods used to monitor the abundance, structure, and health of the bighorn sheep population; such presentation was prepared based on the work of Burnham [40], Conroy et al [41], Guerrero et al [42], and Perry et al [43].…”
Section: First Workhop: Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Utilizar dos cámaras en cada estación de muestreo. Si bien algunos trabajos han logrado determinar el ICC utilizando tres regiones corporales (Guerrero-Cárdenas et al, 2020), el tener varios registros de un mismo evento fotográfico podría ayudar a que el ICC sea más preciso. (5) Realizar futuras evaluaciones de condición corporal aplicando simultáneamente el método original y el modificado en este estudio, comparando los resultados obtenidos entre ambos.…”
Section: Issn Online 2007-9621unclassified
“…El índice de condición corporal (ICC) (BCS, por sus siglas en inglés) es un método subjetivo para evaluar la grasa corporal almacenada en el cuerpo de animales, el cual se desarrolló primero en ovejas y posteriormente se adaptó para bovinos (Edmonson et al, 1989). Desde entonces se ha utilizado en una gran cantidad de ungulados domésticos y silvestres, ya que es una manera no invasiva de evaluar la salud de los ejemplares y su estado nutricional (Guerrero-Cárdenas et al, 2020). El ICC en estudios de conservación proporciona información predictiva sobre la calidad del hábitat y la reproducción, lo que ayuda a los manejadores de recursos naturales en la toma de decisiones (Stevenson & Woods, 2006).…”
Section: Introductionunclassified